2019
DOI: 10.1093/oso/9780190846282.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Cracks in the Ivory Tower

Abstract: Ideally, universities are centers of learning, in which great researchers dispassionately search for truth, no matter how unpopular those truths must be. The marketplace of ideas assures that truth wins out against bias and prejudice. Yet many people worry that there's rot in the heart of the higher education business. This book reveals the problems are even worse than anyone suspects. Marshalling an array of data, the authors systematically show how contemporary American universities fall short of these ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…In recent years, some philosophers and social scientists have expressed doubts about the efficacy of education in improving reasoning skills, critical thinking, or moral virtues (Deresiewicz, 2015;Caplan, 2018;Brennan and Magness, 2019). Although empirical research in these domains is scarce (El Soufi and See, 2019;Tuononen et al, 2022), we are not convinced that this scepticism reflects the overall trends reported in the scientific literature.…”
Section: Efficacy Of Teaching Broad Epistemic Integritymentioning
confidence: 92%
“…In recent years, some philosophers and social scientists have expressed doubts about the efficacy of education in improving reasoning skills, critical thinking, or moral virtues (Deresiewicz, 2015;Caplan, 2018;Brennan and Magness, 2019). Although empirical research in these domains is scarce (El Soufi and See, 2019;Tuononen et al, 2022), we are not convinced that this scepticism reflects the overall trends reported in the scientific literature.…”
Section: Efficacy Of Teaching Broad Epistemic Integritymentioning
confidence: 92%
“…As early as President Eisenhower’s military industrial complex speech (Ledbetter, 2011), observers have raised concerns that external funding has shifted higher education missions from serving undergraduates to revenue maximizing research, and administrative compliance supporting that research, and to satisfy ever growing public regulations affecting any institution taking public funding. This has led to an ever-thicker higher education administrative class (Brennan & Magness, 2019; Ginsburg, 2011; Greene, 2010). Further, perhaps ironically, the neoliberal reforms of higher education linking funding with measured results have led colleges and universities, including private institutions, to focus more on prestige seeking behaviors raising official rankings, as indeed some university presidents (e.g., Trachtenberg, 2012) and journalists (Washington Monthly editors, 2013) lament, and to enhance public relations functions such as college athletics (Levine, 2014).…”
Section: The Rise Of the All-administrative Universitymentioning
confidence: 99%
“…Further, faculty growth has come disproportionately among adjunct and renewable contract rather than tenured or tenure track posts, generally undermining the ability of faculty to challenge large and well-compensated administrative staff (Cross & Goldenberg, 2009; Smith, 2015). Indeed Brennan and Magness (2019) speculate that administrators prefer adjunct faculty since they are more compliant, and subject to downsizing before administrators.…”
Section: The Rise Of the All-administrative Universitymentioning
confidence: 99%
See 2 more Smart Citations